BUILDING LEADERSHIP CHARACTER THROUGH STUDENT ORGANIZATION: A CASE STUDY AT KH. MAS MANSYUR INTERNATIONAL BOARDING SCHOOL 2020/2021 - Dini Pandu Primawan; Nurul Latifatul Inayati; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2020)
Pesantren Mahasiswa (PESMA) KH Mas Mansur belongs to Universitas Muhammadiyah Surakarta. It is a dormitory for higher students both local and international students. It has two organizations, namely the Central for International Student Organization (ISO) and Ikatan Mahasiswa Muhammadiyah (IMM) Commissariat of the KH Mas Mansur International Boarding School. This study aims to determine how far the student organization plays an effective role in instilling the leadership character of the student. This is both quantitative and qualitative research with Sequential Explanatory. The sample is 44 students of 127 members of the Central ISO and the IMM Commissariat of the KH Mas Mansur International Boarding School. The results of this study can be concluded that there is a significant influence between student organizations on the lead character for PESMA KH Mas Mansur. This is indicated by the percentage of influence exerted by the student organization on the lead character of the students at 39.5% while 60.5% is influenced by other variables. The most probable results also due to the clear vision and mission of the student organization based on Islamic values and then it is implemented through various activities at PESMA.